Dead Girls Don't Say Sorry - Ritany, Alex (New York : Alfred A. Knopf, 2024)
Navigating toxic friendships, grief, and the complexities of growing up, Nora's life takes a tragic turn when her best friend Julia dies, leaving her to unravel the secrets and lies hidden in their friendship.
Ages 14 up.
Grades 10-12.
Keywords: Friendship -- Young adult; Death -- Young adult fiction; Secrecy -- Young adult fiction; Grief -- Young adult fiction; Schools -- Young adult fiction; Friendship -- Young adult fiction; Death -- Young adult fiction; Secrets -- Young adult fiction; Schools -- Young adult fiction; Bildungsromans; Psychological fiction; School fiction; Novels; Young adult fiction